Surgical Site Infections After Routine Syndesmotic Screw Removal: A Systematic Review. Issue 4 (April 2021) - Sanders, Fay R. K.; Birnie, Merel F. N.; Penning, Diederick; Goslings, J. Carel; Schepers, Tim
Abstract : Objectives: To investigate the incidence of surgical site infections (SSIs) after routine removal of syndesmotic screws (SSs) placed to stabilize syndesmotic injuries. Data sources: A systematic literature search was performed in the PubMed, Cochrane, and EMBASE databases for studies published online before February 2020, using the key words and synonyms of "syndesmotic screw" ("ankle fractures" or "syndesmotic injury") and "implant removal." Study Selection: Studies were eligible for inclusion when they described >10 adult patients undergoing elective/scheduled removal of the SS. Data extraction: The 15 included articles were assessed for quality and risk of bias using the Newcastle–Ottawa Scale. Baseline characteristics of the studies, the study population, the intervention, the potential confounders, and the primary outcome (% of SSIs) were extracted using a customized extraction sheet. Data synthesis: The primary outcome was presented as a proportion of included patients and as a weighted mean, using inverse variance, calculated in RStudio. Furthermore, potential confounders were identified. Conclusions: The percentage of SSIs ranged from 0% to 9.2%, with a weighted mean of 4%. The largest proportion of these infections were superficial (3%, 95% confidence interval: 2–5), compared with 2% deep infections (95% confidence interval: 1–4). These rates were comparable to those of other foot/ankle procedures indicating that the individual indication for SS removal (SSR) should be carefully considered. Future studies should focus on valid indications for SSR, the influence of prophylactic antibiotics on an SSI after SSR, and complications of retaining the SS to enable a fair benefits/risks comparison of routine versus on-demand removal of the SS. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.